Comparative study of the effect of preoperative clonidine and tranexamic acid on the rate of bleeding in lumbar spine surgery - Dr. Mehrdad Masoudifar, Dr. Monadi Hamidfar, Dr. Zahra Rahimi (Drugs and Cell Therapies in Hematology, 2021)
Introduction & Objective: Reducing intraoperative bleeding in lumbar spine fusion surgery reduces the need for infusion of blood and blood products and reduces the risk of complications of blood transfusions such as hemolytic and non-hemolytic reactions, acute lung injury, viral and bacterial infections, hypothermia and coagulation disorders. In this research, we performed a comparative study of the effect of clonidine and tranexamic acid before surgery on the amount of bleeding in lumbar spine surgery. Method: This is double-blind randomized clinical trial with a control group. After obtaining the consent, we selected 90 ASA patients of class 1 and 2 and aged between 20-65 years, who underwent decompression surgery and lumbar spine fixation in Alzahra Hospital and Medical Center in Isfahan (2019-2020). We divided them into three groups: C, T, and P. Patients of the group C receive clonidine, patients of the group T receive tranexamic acid, and patients of the group P receive placebo. We collected and analyzed the data using repeated measures tests and one-way analysis of variance at a significance level of 0.05. The used software was SPSS version 24. Results: The results of this research showed that the difference between the duration of surgery and the duration of extubation is not significant between the three groups. There is no significant difference in the duration of recovery period; it is shorter only in the tranexamic acid group. In bleeding, the difference is significant in all three groups. The volume of bleeding in the placebo group is more than the other two groups. There is a significant difference in clonidine and tranexamic acid, but there is not much difference between the two groups. In terms of Likert criterion, there is also a significant difference between the three groups regarding surgeon satisfaction. There is not much difference between placebo and clonidine and there is more satisfaction with tranexamic acid. There is also a big difference between clonidine and tranexamic acid. SBP is significantly different between groups. There is a significant difference in the placebo group but it is not so in the other two groups. DBP is significantly different between the groups. There is a significant difference between placebo and tranexamic acid groups, but no significant difference in clonidine group. HR is significantly different between groups. There is a significant difference in the placebo group, but it is not so in the other two groups.